Definition of the complex Monge-Ampère operator for arbitrary plurisubharmonic functions - Sadullaev, Azimbay (Eurasian Mathematical Journal, 2012)
In this paper we consider the problem of definition of the Monge-Ampère operator for an arbitrary plurisubharmonic function. The paper has a survey character; in it we discuss the results related to this area. We give one construction of the definition of the Monge-Ampère operator, which will then be applied to maximal plurisubharmonic functions.